L'Europe des Peintres - Bosquet, Alain; Galerie Isy Brachot, Bruxelles (Bruxelles : Galerie Isy Brachot, 1979)
Alechinsky, Pierre ; Appel, Karel ; Bacon, Francis ; Bogart, Bram ; Burssens, Jan ; Corneille ; Cremonini, Leonardo ; Delvaux, Paul ; Freddie, Wilhem ; Gentilini, Franco ; Graas, Gust ; Guarienti, Carlo ; Klapheck, Konrad ; Labisse, Félix ; Le Brocquy, Louis ; Manessier, Alfred ; Peverelli, Cesare ; Soulages, Pierre ; Stern, Bernard ; Strebelle, Olivier ; etc.
L'Europe des Peintres, Galerie Isy Brachot, Bruxelles, 31 mai - 22 septembre 1979
boek